Two dimensional simulations of triode VHF SiH4 plasma. (11th April 2018) - Su, Li-Wen; Chen, Weiting; Uchino, Kiichiro; Kawai, Yoshinobu
Abstract: Two-dimensional simulations of a triode VHF SiH4 plasma (60 MHz) were performed using a fluid model, where the plasma was realized using multirod electrodes. Higher-order silanes that are responsible for the quality of amorphous silicon were included in the simulations. A typical VHF plasma with an electron density higher than 10 16 m −3 and an electron temperature lower than 3 eV was predicted between discharge electrodes while the electron density near the substrate was very low. The SiH3 density was fairly uniform between discharge electrodes and did not decrease rapidly near the substrate, suggesting a high-speed deposition. Higher-order molecules and radicals that play an important role in dust formation had similar spatial profiles and their densities were five to 6 orders of magnitude lower than the SiH3 density. We discussed the effect of the rate constant of reaction, SiH3 + SiH3 → SiH2 + SiH4, on the SiH3 density.